2007
DOI: 10.1007/s00101-006-1124-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous puncture in preclinical emergency medicine

Abstract: The IO infusion technique is a simple, fast and safe alternative method for emergency access to the vascular system in children < or =6 years of age in the prehospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 27 publications
1
3
0
4
Order By: Relevance
“…Although the EMS paramedics are trained in intraosseous access, it is not widely applied: only 31% of all intraosseous access was provided by the EMS paramedics. The infrequent use of intraosseous infusion compared to other advanced life support skills in hospital and by paramedics and HEMS has been described [12,13]. Still, several studies have shown that the placement of an intraosseous line is easy, fast and has a high success rate [14-16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the EMS paramedics are trained in intraosseous access, it is not widely applied: only 31% of all intraosseous access was provided by the EMS paramedics. The infrequent use of intraosseous infusion compared to other advanced life support skills in hospital and by paramedics and HEMS has been described [12,13]. Still, several studies have shown that the placement of an intraosseous line is easy, fast and has a high success rate [14-16].…”
Section: Discussionmentioning
confidence: 99%
“…Zum anderen bestehen Unterschiede zwischen dem bodengebundenen und luftgestütz-ten Rettungsdienst: Für bodengebundene Notarztsysteme wird die Häufigkeit päd-iatrischer Notfallsituationen mit etwa 3-6% angegeben, für den luftgestützten Rettungsdienst mit rund 11-13% [9,10,12,16,18,25]. In diesem Zusammenhang ist insbesondere eine multizentrische Studie, die Daten sämtlicher Luftrettungsstütz-punkte des ADAC sowie des Bundesinnenministeriums beinhaltet und somit einen annähernd bundesweiten Überblick erlaubt, erwähnenswert [25]: Der Anteil pädiatrischer Notfälle lag in dieser Untersuchung bei 12,9% (Erfassungszeitraum 2001 bis 2003).…”
Section: Häufigkeit Pädiatrischer Notfälleunclassified
“…Zudem zeigt ein Vergleich mit vorangegangenen Analysen der RTH-Station "Christoph 22" aus den Zeiträumen von 1993 bis 1997 und 1996 bis 2005, dass der Anteil an "traumatologischen" Notfällen stabil geblieben ist (61 bzw. 54%; [16,18]). Unter Berücksichtigung der verschiedenen Altersgruppen spielt der traumatologische Notfall bei Säuglingen eine untergeordnete Rolle.…”
Section: Einsatzspektrumunclassified
See 1 more Smart Citation
“…Die intraossäre Infusionstechnik hat sich in der pädiatrischen Notfallmedi zin seit Jahren als schnelle, effiziente und sichere Alternativmethode zur Schaffung eines Gefäßzugangs erwiesen, um einem vitalgefährdeten Kind dringend benöti gte Medikamente und Flüssigkeiten zu ap plizieren [21,51].…”
Section: Grundlagenunclassified